Physico-chemical characteristics of Ca/P ratio on the composition and structure of oxygenated apatite - Jerdioui, S.; Bouammalia, H.; Mejdoubi, E.; Touzani, R.; Azzaoui, K.; Hammouti, Belheir; Sabbahi, R.; Nandiyanto, Asep Bayu Dani; Elansari, L. L. (Communications in Science and Technology, 2024)
Phosphocalcic apatites have osteoconductive and bioactive properties that make them suitable for bone reconstruction. But, they are inactive against pathogenic microorganisms that can infect bone tissue. To overcome this limitation, we synthesized oxygen-doped phosphocalcic apatites that can release molecular oxygen as a bioactive molecule. We investigated how the calcium-to-phosphorus ratio (Ca/P) gave impacts on the chemical and structural composition of the oxygen-doped phosphocalcic apatites. We here used the double decomposition method, which involved mixing calcium nitrate and diammonium phosphate solutions in an ammonia buffer. We then characterized the products using several analysis, including infrared absorption spectroscopy, X-ray diffraction, thermal analysis, nitrogen adsorption-desorption, and elemental chemical analysis. It was found that the oxygen-doped phosphocalcic apatites were calcium-deficient and had a well-defined crystallinity at room temperature. After calcination at 900°C, the crystallinity improved further. The thermal analysis showed two mass losses: one at 50°C due to water adsorption and another at 450°C due to CO2 release. The specific surface area was about 100 ± 2 m2/g without any change with the Ca/P ratio. The quantity of molecular oxygen increased with the Ca/P ratio and reached an optimal value of the order of 3.6 ×10-4 mol for Ca/P=1/65 with the chemical formula of Ca9.9(PO4)6(OH)1.25(O2)0.74(CO3)0.01. It is important to make further analysis to know more about the properties of oxygenated apatite, and to combine this apatite with polymers purposely to have biomedical composites. It then can be concluded that the oxygen-doped phosphocalcic apatites could be a promising biomaterial for bone infection prevention and treatment. This research highlights an oxygenation treatment of phosphocalcic apatite and brings new ideas and possibilities for future research and development to get better understanding of the behavior of these biomaterials to be more effective, especially in the biological field. As a perspective, improving the biological properties in these biomaterials needs to be further explored, including experimental parameters for the obtainment of more conclusive results.